Workshop on Enhancing the Capacity of Science Teachers through the Utilization of Local Potential and Science Process Skills in Garut Regency - Wiwit Yuli Lestari; Andinisa Rahmaniar; Abdul Latip; Shinta Purnamasari; Putri Nurul Fitriyyah; Selly Selpiana (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
Local potential refers to the various resources available within a particular region that can be utilized as learning resources in science education to strengthen the connection between scientific concepts and students’ surrounding environment. This community service activity was conducted through a workshop on the integration of local potential and science process skills for science teachers in Garut Regency. The activity involved 26 science teachers who participated in material presentations, discussions, and an evaluation using a participant response questionnaire. The questionnaire results indicated highly positive responses, with 92.30% of participants strongly agreeing that the resource person demonstrated mastery of the material, 100% strongly agreeing with the opportunity provided for discussion, 88.46% strongly agreeing with the clarity of the material delivery, and 84.61%–100% strongly agreeing with the usefulness of the activity, the relevance of the material, and its applicability to science learning. The findings indicate that participants perceived the workshop as beneficial in strengthening their understanding of the integration of local potential and science process skills. In addition, participants expressed positive responses regarding the relevance of the materials to their instructional needs and their potential application in contextual and meaningful science learning in schools. The results of this activity indicate that the field-needs-based workshop was very well received by the participants and has the potential to support the professional development of science teachers by strengthening their knowledge, motivation, and reflection on environment-based teaching practices.